2012
DOI: 10.1021/ic202702r
|View full text |Cite
|
Sign up to set email alerts
|

Structural Influence on the Photochromic Response of a Series of Ruthenium Mononitrosyl Complexes

Abstract: In mononitrosyl complexes of transition metals two long-lived metastable states corresponding to linkage isomers of the nitrosyl ligand can be induced by irradiation with appropriate wavelengths. Upon irradiation, the N-bound nitrosyl ligand (ground state, GS) turns into two different conformations: isonitrosyl O bound for the metastable state 1 (MS1) and a side-on nitrosyl conformation for the metastable state 2 (MS2). Structural and spectroscopic investigations on [RuCl(NO)py(4)](PF(6))(2)·1/2H(2)O (py = pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 59 publications
(75 reference statements)
4
83
0
Order By: Relevance
“…There has been a prior assumption that, for each crystal system, there is a fixed overall level of achievable MS occupation, bound either by the steric properties of the crystal or the electronic properties of the active molecule. 4,8,32,33 This study challenges that supposition, and the observation of temperature-regulated photo-activation adds a new dimension of control for single-crystal-to-single-crystal linkage isomer transformations, which may be exploited in future device technologies. Importantly, in terms of crystal engineering, the inclusion of hydrogen bond donor groups need not be avoided, a factor that will assist in the targeted design of new linkage isomer systems aimed towards specific photoswitching applications.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There has been a prior assumption that, for each crystal system, there is a fixed overall level of achievable MS occupation, bound either by the steric properties of the crystal or the electronic properties of the active molecule. 4,8,32,33 This study challenges that supposition, and the observation of temperature-regulated photo-activation adds a new dimension of control for single-crystal-to-single-crystal linkage isomer transformations, which may be exploited in future device technologies. Importantly, in terms of crystal engineering, the inclusion of hydrogen bond donor groups need not be avoided, a factor that will assist in the targeted design of new linkage isomer systems aimed towards specific photoswitching applications.…”
Section: Discussionmentioning
confidence: 91%
“…1 Photo-switching between linkage isomers can be achieved in both solution and the solid-state, with irradiation of the solid leading to the production of a metastable state (MS) isomer below some critical temperature. 2 In situ photocrystallographic studies have to-date revealed the structures of various MS linkage isomers, including nitrosyl, 3,4 nitrite, [5][6][7][8] sulfur dioxide, [9][10][11] and di-nitrogen 12 systems.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Previous studies have highlighted the influence that the surrounding crystalline environment can have on the progress of the photoreaction. 9,20,51 Intermolecular interactions involving the isomerising ligand are particularly influential, as these must be broken and/or (re)formed to facilitate the atomic rearrangements necessary for photoswitching to occur. Our recent work has highlighted the important effect that hydrogen bonding to the nitrite ligand can have on the nitro " nitrito process, 19,51 leading us to consider how intermolecular interactions can influence the photoswitching kinetics in 1.…”
Section: B Nitro-to-nitrito Photo-excitation Kinetic Studiesmentioning
confidence: 99%
“…The earliest photocrystallographic studies with linkage isomers were carried out on metal-nitrosyl complexes, including seminal work by Coppens et al on sodium nitroprusside. 5 Since then, several linkage isomer switches have been studied using photocrystallographic methods, including nitrosyl, [6][7][8][9] sulfur dioxide [10][11][12][13] and nitrite [14][15][16][17][18][19] compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Ruthenium nitrosyl complexes can either induce photochromism (Schaniel et al, 2007b) or NO photorelease (Rose & Mascharak, 2008). In the first case, photoisomerization along the rutheniumnitrosyl bond (Ru-NO/Ru-ON) is observed in the solid state when the compounds are irradiated in the blue region (Schaniel et al, 2007a;Cormary et al, 2009Cormary et al, , 2012. It offers technological applications as optical high-capacity storage devices (Imlau et al, 1999).…”
Section: Structure Descriptionmentioning
confidence: 99%